Synergistic potential of nutraceuticals: mechanisms and prospects for futuristic medicine. Issue 11 (19th November 2020) - Leena, M. Maria; Silvia, M. Gnana; Vinitha, K.; Moses, J. A.; Anandharamakrishnan, C.
Abstract : Synergistic potential of nutraceuticals in chronic disease management. Abstract : Nutraceuticals are valued for their therapeutic effects and numerous health benefits. In recent years, several studies have demonstrated their superior performances when co-delivered; the concept of synergism has been established for various bioactives. Apart from improvements in the bioavailability of partnering compounds, this approach can protect the radical scavenging potential and biological effects of individual compounds. In this review, the intricate mechanisms that promote synergistic effects when bioactive compounds are co-delivered are detailed. Importantly, a range of potential medical applications that have been established through such synergistic effects is presented, emphasizing recent developments in this field. Also, a section has been devoted to highlighting perspectives on co-encapsulation at the nanoscale for improved synergistic benefits. While prospects for the treatment of chronic diseases are well-demonstrated, several challenges and safety concerns remain, and these have been discussed, providing recommendations for future research.